Carrying the Pox: The Use of Children and Ideals of Childhood in Early British and Imperial Campaigns Against Smallpox. (7th April 2015) - Murdoch, Lydia
Abstract: Recent scholarship has done much to advance the history of smallpox inoculation and vaccination, but the human carriers used to convey the live lymph from place to place call for more attention. Most were children, and their histories demonstrate how new concepts of childhood proved instrumental in the extension of medical developments and global imperial networks. This essay examines the children used to transmit anti-smallpox technologies, staring with Lady Wortley Montagu's popularization of inoculation in England in the eighteenth century and extending through British efforts to bring cowpox vaccination to South and East Asia in the early 1800s. Emerging ideals of child innocence helped establish inoculation and vaccination as safe and effective treatments across distinctions of race, class, and place. At the same time, however, medical professionals reinscribed hierarchies of class and race upon children's bodies. Elite, white children saved from smallpox especially became associated with ideals of parental, domestic affection, while working-class, orphan, and indigenous children more often served the role of children of the state—the test subjects and global carriers of both vaccine matter and the ideals of liberal imperialism.